No clinical benefit from manual thrombus aspiration in patients with non-ST-elevation myocardial infarction - Siudak, Zbigniew; Dziewierz, Artur; Rakowski, Tomasz; Tokarek, Tomasz; Mielecki, Waldemar; Żabówka, Anna; Plens, Krzysztof; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : There are scarce data on the usefulness of manual thrombectomy among patients with non-ST-elevation myocardial infarction (NSTEMI). Early positive reports were not supported by the clinical outcome in the recent TATORT-NSTEMI (Thrombus Aspiration in Thrombus Containing Culprit Lesions in Non-ST-Elevation Myocardial Infarction) study. Aim : To analyze the long-term outcome of NSTEMI patients treated with manual thrombectomy during percutaneous coronary intervention (PCI) in the Polish multicenter National Registry of Drug Eluting Stents (NRDES) study. Material and methods : There were 13 catheterization laboratories in Poland that enrolled patients in NRDES Registry in 2010–2011. Patients with a diagnosis of NSTEMI were divided into two groups: those that were treated with manual thrombectomy for their primary PCI (T) and those who were not (NT). Results : There were 923 patients diagnosed with NSTEMI in NRDES. Aspiration thrombectomy was used in 71 (7.7%) patients and the remaining 852 (92.3%) NSTEMI cases were treated without thrombectomy during the index PCI. Thrombectomy was more often used in patients with TIMI less than 1, thrombus grades 4 and 5 and older male patients. Percutaneous coronary interventions complications such as distal embolization and slow flow were more often observed in the thrombectomy subgroup. Overall mortality at 1 year was 1.69% in the T and 5.92% in the NT group (p = 0.24 and p = 0.32 after propensity score matching adjustment with p = 0.11 in the multivariate logistic regression model). Conclusions : There was no mortality benefit from thrombus aspiration in NSTEMI patients at 1-year follow-up.